O leitor e a literatura juvenil : um diálogo entre os prêmios literários Jabuti e FNLIJ e o Programa Nacional Biblioteca da Escola - Guerra, Mariana Passos Ramalhete (2015)
This paper is bound to the research line ―Educação e Linguagens‖ (Education and Languages) and is part of the studies of the research group entitled ―Literatura e Educação‖ (Literature and Education) at Universidade Federal do Espírito Santo (Federal University of Espírito Santo).The studylooks into public data related to the works which were simultaneously awarded bythe Jabuti Award(PrêmioJabuti)– from the Brazilian Book Chamber(CâmaraBrasileira do Livro) – and the FNLIJ Award (Fundação Nacional do LivroInfantil e Juvenil – National Foundation of Infantile and Juvenile Books) compared to the works selected by the PNBE (Programa Nacional Biblioteca da Escola – National Program of School Libraries), comprehending the period between the years 2004 and 2013. This paper aims at discussing whether the opinion of the members of the jury of the Jabuti Awardthe FNLIJ Award indicates a profile model of the literary work and, therefore, of the reader, when compared to PNBE. In order to do so, the books O Fazedor de Velhos (The Maker of Old People), by Ricardo Lacerda (2008) and Lis no peito: um livro que pedeperdão (Liz in the chest: a book that apologizes), by João Miguel Marinho (2005) were selected as privileged corpus for the analysis, since they were simultaneously approved by the three aforementioned instances, which are quite relevant for the juvenile literature (the literary awards granted by a specialized jury and by the official program). Methodologically characterized as a bibliographical and documental research, and through the analysis of the previously mentioned corpus whose theoretical references are based on AntônioCândido‘sliterary system (1999; 2000), Pierre Bourdieu‘s literary field (1996; 2013) and Roger Chartier‘scommunity of readers (1994; 1999; 2002a; 2002b; 2011; 2015), this study observed that the editorial market plays a decisive role in book publishing, considering its insertion in the cultural industry logic. Thus, the analysis of the books made it possible to verify that the profile of the juvenile works as well as that of the juvenile reader keep an absence of a more acute and critical social and economic perspective in its scenario. Moreover, the profile lays emphasis on the the bourgeois teenage universe and therefore conjectures a view of literature that is somewhat romanticized, redeemable and salvationist